Pemberdayaan UMKM melalui Pendampingan Penyusunan Laporan Keberlanjutan: Pendekatan Partisipatif dalam Meningkatkan Daya Saing Berkelanjutan: Indonesia - Laksmi, Ayu Chairina; Tumewang, Yunice Karina; Ardiami, Kinanthi Putri; Tatik; Wicaksono, Aditya Pandu; Octavio, Muhammad Fadhly Rizky; Mustofa , Ikrom (Jurnal Abdimas Madani dan Lestari (JAMALI), 2026)
Sustainability issues have become a central concern in contemporary business practices, including within the Micro, Small, and Medium Enterprises (MSMEs) sector, driven by increasing stakeholder demands for environmental, social, and governance (ESG) performance. Brownies Cinta MSME, as a rapidly growing enterprise in Indonesia, demonstrates significant economic potential but faces challenges related to production waste management, energy consumption, and social responsibility. To date, the enterprise has not developed a sustainability report as a formal instrument to measure and communicate its sustainability performance. This community engagement initiative aims to enhance the capacity of Brownies Cinta MSME to understand and prepare a sustainability report based on the Global Reporting Initiative (GRI) Standards. The program employed a collaborative approach through online training and mentoring involving the MSME partner and the University of Southampton. Data were collected using a triangulation method, combining questionnaires, in-depth interviews, direct observation, and Focus Group Discussions (FGDs), with a particular emphasis on environmental (GRI 300) and social (GRI 400) aspects. The data were analyzed using descriptive and qualitative approaches within the GRI framework, complemented by a materiality assessment to identify the most relevant sustainability issues. The results indicate an improvement in the partner’s understanding of sustainability practices and the successful development of a draft sustainability report aligned with GRI Standards. This initiative is expected to support the implementation of sustainable business practices and strengthen MSMEs’ transparency and accountability toward their stakeholders.